Peningkatan Peningkatan Hasil Belajar Bahasa Indonesia Melalui Model PBL Berbantu Media Visual pada Siswa Kelas IV SD: Peningkatan Hasil Belajar Bahasa Indonesia Melalui Model PBL Berbantu Media Visual pada Siswa Kelas IV SD - Ardini Kartika Cahyaningrum; Mira Azizah; Darsino (UNIB Press, 2024)
The aim of this research is to determine the improvement in Indonesian language learning outcomes using the Problem Based Learning (PBL) model assisted by Visual media for class IV students at SDN Plamongansari 02 Semarang. The techniques used in collecting data in this research were tests and observation. Tests are used to measure student learning outcomes, the data of which is obtained based on the results of students' work on evaluation questions given by the teacher. then carry out an initial test, then go to cycle 1 and cycle 2. Data analysis techniques are obtained through quantitative descriptive data analysis techniques. Data processing and data analysis uses the calculation of average scores and percentage of learning completeness. Based on the results of research that has been carried out, data shows that the pre-cycle results were 54.1%, there was an increase in the first cycle of learning completeness by 70.8% and an average score of 76.8. In cycle II, the percentage of complete learning outcomes was 83.3% and the average score was 81.1. It can be concluded that the use of the Problem Based Learning (PBL) learning model, assisted by visual media in the form of PowerPoint can improve Indonesian language learning outcomes for class IV students at SDN Plamongansari 02.